1991
DOI: 10.1007/bf03258258
|View full text |Cite
|
Sign up to set email alerts
|

Animal Pharmacology of Nebivolol

Abstract: SummaryNebivolol is a mixture of equal amounts of 2 enantiomers: SR3-nebivolol (d-nebivolol) and RS3-nebivolol (I-nebivolol). SR3-nebivolol is a potent and selective PI-adrenergic antagonist both in vitro and in vivo. Nebivolol acutely lowers blood pressure in spontaneously hypertensive rats and induces a slight decrease in total peripheral vascular resistance and a slight increase in cardiac output in anaesthetised dogs. These haemodynamic effects cannot be explained by PI-adrenergic antagonism and are largel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Previous studies have shown remarkable vasodilating effects with minimal alterations of the metabolic profile. 22,23 However, there is little information available on its pharmacological effects in physically active hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown remarkable vasodilating effects with minimal alterations of the metabolic profile. 22,23 However, there is little information available on its pharmacological effects in physically active hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 A number of experimental and human pharmacological studies suggest that the vasodilatation is triggered via the endothelial nitrogen oxide system. The pharmacological profile is characterised by the significant antihypertensive effects as well as a lowering of cardiac pre-and after-load.…”
Section: Journal Of Human Hypertension (2001) 15 715-721mentioning
confidence: 99%
“…Numerous biologically active natural products contain the butyrolactone ring system (77). Similarly, methyl α-aryl-α-ketoacetates (97) have been reduced to methyl (R)- (98) or (S)-mandelates, useful intermediates in the synthesis of, among other compounds, optically active 4-aryl-2-hydroxytetronic acids (99) (78). These acidic compounds are aci-reductones which possess a low redox potential and numerous biological activities including reactive radical scavenging, cyclooxygenase inhibition, and antilipidemic properties.…”
Section: Asymmetric Induction Methodologiesmentioning
confidence: 99%
“…The hemodynamic effects cannot be explained by β 1adrenergic antagonism of the (+ )-isomer and this effect is not shared by other β-blockers. The mechanism of the observed synergy between the two enantiomers is not known (98).…”
Section: Antihypertensive Agentsmentioning
confidence: 99%
“…Nebivolol is cardioselective, demonstrating very high affinity for the β 1 receptor and a 50-fold lower affinity for β 2 receptors [8]. The drug is a racemic mixture of two enantiomers, dand l-nebivolol [9]. The β 1 blocking activity of the agent resides in d-nebivolol, which shows a more than 100-fold greater affinity for β 1 receptors compared to l-nebivolol.…”
Section: Nebivololmentioning
confidence: 98%